(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Climate change, depletion of natural resources, social inequality and poverty, a lack of food resources, etc. issues related to world sustainable development has become increasingly relevant in the last 50 years, negatively affecting people's opportunities, and living standards in various countries. Despite these problems, the average level of wealth of the population in the world is gradually increasing over time. Considering forecasts on population growth by the end of the 21st century, it must be admitted that the current world-dominant linear economic model is fully unsustainable in resource consumption, as there is a natural barrier to economic growth. The aim of the present research study is to explore the potential of the circular economy as a tool for achieving sustainable development, based on a theoretical framework. This paper was built based on a broad literature review to examine the limitations and conceptual gaps of the circular economy concept as a tool for achieving sustainable development. It has been concluded that the circular economy concept undeniably has huge potential to promote sustainability within planetary boundaries as well as it can be implemented to decouple economic growth from the utilization of finite resources. However, a broader analysis of the circular economy concept allows us to assert that to date, a clear and effective approach for the transition to this economic model, affecting all areas of sustainable development (i.e. environmental, economic, social) has not been developed. In addition, the circular economy concept is still evolving, there is a tendency to view the circular economy concept holistically, covering various sub-concepts of the circular economy under the common Sustainable Circular Economy concept's umbrella.